2022
DOI: 10.1097/mcp.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in chronic obstructive pulmonary disease

Abstract: Purpose of reviewThere is biological and epidemiological evidence supporting a role for vitamin D in the respiratory system, and vitamin D deficiency (VDD) may be associated with poor health outcomes in people with chronic obstructive pulmonary disease (COPD). This review summarizes recent findings relevant to the role of vitamin D in COPD.Recent findingsThe prevalence of VDD in people with COPD may be underestimated. Treatment of severe VDD [serum 25(OH)D3 < 10 ng/ml] may reduce the risk of COPD exacerbations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The results are similar to the research results of Li et al (19). In addition, according to related studies (20,21), VitD deficiency will also impact lung function. Therefore, this study also analyzed the VitD level in participants, and revealed a notably higher 25(OH)D level in the control group than that in the research group, indicating a severe decrease in VitD level in patients with COPD, which may be bound up with the fact that the damaged liver and kidney function in patients with COPD impacts the synthesis of VitD.…”
Section: Clinical Diagnostic Value Of Il-1β and 25(oh)d For Aecopdsupporting
confidence: 90%
“…The results are similar to the research results of Li et al (19). In addition, according to related studies (20,21), VitD deficiency will also impact lung function. Therefore, this study also analyzed the VitD level in participants, and revealed a notably higher 25(OH)D level in the control group than that in the research group, indicating a severe decrease in VitD level in patients with COPD, which may be bound up with the fact that the damaged liver and kidney function in patients with COPD impacts the synthesis of VitD.…”
Section: Clinical Diagnostic Value Of Il-1β and 25(oh)d For Aecopdsupporting
confidence: 90%
“…Low serum 25-hydroxycholecalciferol levels have been linked to poor asthma control, and supplementation with this compound has been shown to improve asthma control in individuals with deficiency (Nitzan et al, 2022;Wang et al, 2022). Low levels in children have been associated with increased asthma frequency, along with deteriorating lung functions and airway hyperresponsiveness (Salmanpour et al, 2022;Mullin & Milne, 2022). Clinical trials among asthmatic subjects have shown the shielding effect of 25-hydroxycholecalciferol supplementation (Luo et al, 2015;Alkhatatbeh et al, 2021;Mullin & Milne, 2022;Nitzan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although it’s widely recognized that vitamin D deficiency frequently plagues patients suffering from COPD, the relationship between serum vitamin D concentrations and COPD and the underlying mechanical interplay continues to be ambiguous. 34 An array of differing viewpoints characterizes the discourse in this area. For instance, research by Camargo suggested that COPD patients who are severely deficient in vitamin D might witness benefits from a regular monthly regimen of vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%